Tindak Tutur Ilokusi dalam Novel Orang-Orang Biasa Karya Andrea Hirata (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This study aims to describe the form of commissive and declarative illocutionary speech acts contained in the novel Orang Biasa by Andrea Hirata, and describe the relevance of the research results to Indonesian language learning in high school. The research design used is descriptive qualitative. The data in this research are texts (words and sentences containing commissive and declarative illocutionary speech acts). The data collection technique was obtained by using reading method and note-taking technique. Data analysis technique is done by identifying, classifying, and describing. Based on John R. Searle's theory, the result shows that there are commissive and declarative illocutionary speech acts in the novel Orang Biasa by Andrea Hirata. Commissive illocutionary speech acts include representative acts, namely: promise, threaten, swear, offer, plan, obligation. Declarative acts, namely: naming, pointing, deciding, cancelling, prohibiting, allowing, and forgiving. The relevance of the research results to Indonesian language learning in high school can be focused on listening skills.